Teleoperation Using Google Glass and AR.Drone - João Marcelo Xavier Natário Teixeira; Ronaldo Ferreira dos Anjos Filho; Matheus Santos; Veronica Teichrieb (Journal on Interactive Systems, 2014)
Nenhum resumo disponível